Systematic map of the most recent evidence (2010–2019) on ruminant production-limiting disease prevalence and associated mortality in Ethiopia - Tsouloufi, Theodora K.; MacVicar, Isla S.; Donnison, Louise M.; Smyth, Karen L.; Peters, Andrew R. (Frontiers in Veterinary Science, 2023)
Background Ethiopia's livestock sector supports the livelihoods of millions of smallholder farmers. However, despite the improvements of recent years, livestock productivity remains low due to critical constraints, including infectious diseases. The aim of this study was to collate and synthesize the published evidence on ruminant disease frequency and disease-associated mortality in Ethiopia, by identifying knowledge gaps and clusters in the literature to provide the basis for a decision-making tool. Methods Searches on both bibliographic and organization databases were conducted in English and were restricted to the period 2010–2019. Search results were screened for relevance at title, abstract and full text level. Results There were 716 articles identified relevant to the research question. The systematic map revealed an increased publication output from 2012–2017, compared to 2010–2011 and 2018–2019. Most studies were conducted in Oromia, Amhara and SNNPR. A substantial body of evidence was found for trypanosomosis, ectoparasite infestation, fasciolosis, nematodiasis, echinococcosis, and brucellosis. Conclusion This study suggests that despite the high output of epidemiological publications, further understanding of a considerable number of diseases is required and where evidence is abundant, synthesis of information should be carried out in order to better inform decisions on disease control priorities in the livestock sector.